Das Präteritum im Alemannischen Südwestdeutschlands - Leonhard, Jens (Zeitschrift für Sprachwissenschaft, 2021)
Zusammenfassung This paper analyses the increase in the use of the preterite in spoken Alemannic in south-western Germany. There are almost no recent studies that explore the preterite in Upper German because of the widespread hypothesis that there is no preterite in Upper German (except for the verb sein ‘to be’) due to the loss of the preterite in Upper German ( Oberdeutscher Präteritumschwund ). In contrast to this, I account for a language change in the timespan from 1974 to 2013 in which the preterite becomes more frequent in relation to the perfect and is now part of the spoken Alemannic in south-western Germany. To account for this, I use a combination of a real time and an apparent time analysis. Additionally, all verbs forming a preterite have a specific semantic value, i. e. an inherent meaning of state. This means they are durative (=the situation lasts for a certain period of time), atelic (=the situation has no terminal point at which the situation is complete) and non-dynamic (=the situation involves no change). Perfect forms on the other hand do not have this specific semantic value.